Ways to overcome aggressive manifestations of wild animals that arise during adaptation through life in society - Stanislavska, Svitlana Andriivna (Global Prosperity, 2025)
Abstract. People and animals have always coexisted. People are part of the animal world, they just sometimes forget about it and consider themselves the masters. Of course, the human part of the animal world is the most developed in the mental plan, which allowed it to move up so rapidly to occupy the top step of the evolutionary process. But animals and people are united by a single giant biocenosis, which, as a dynamic system, balances, maintaining equilibrium due to the correct interaction of its components. The fall of one brick of this giant structure, which is the animal world, will cause its destruction. Man is so actively, deeply and quickly interfering in the world of wildlife, occupying more and more territories for housing and his professional activities, which previously belonged entirely to wild animals, that they do not have time to adapt to the conditions of the presence of people and the conditions of ethnic location, which were changed by people in the process of activity. Humanity cannot be stopped in its desire for development in all understandings and manifestations. But it is imperative for people to realize that, dominating the animal kingdom and using their habitats, they must help wild animals adapt to changes caused by human activity in a territory that does not belong to them. Adaptive methods of establishing relationships should be used to build a balanced coexistence with wild animals. Using the example of the socialization of wild cats of South Africa (servals), some points that should be paid attention to and used when socializing servals are considered and suggested in order to avoid aggressive manifestations caused by human interference in the personal space of these animals.